OPPOSITION POLITICS AND DEMOCRATIC STABILITY IN NIGERIA AND GHANA: A COMPARATIVE ANALYSIS, 2011-2022 - Abia, Ifeoma Lillian; Ifedi, Francisca Obiageli (University of Nigeria Journal of Political Economy, 2024)
This study compared opposition politics and democratic stability in Nigeria and Ghana, between 2011 and 2022. Utilizing the Marxist theory of the state, ex-post-factoresearch design, qualitative method of data collection and qualitative method of data analysis, the study investigated the link between weak structure of election management body and repression of opposition political parties by the ruling party; repression of opposition political parties by the ruling party and electoral violence; as well as manipulation of electoral processes and power alternation between the ruling party and opposition political parties in Nigeria and Ghana. The study found weak structure of election management body to account for the repression of opposition political parties by the ruling party more in Nigeria than in Ghana. The study equally observes that incumbent use of security operatives to intimidate opposition political parties give rise to electoral violence more in Nigeria than in Ghana. Finally, the study observes that the ruling party’s manipulation of electoral processes undermine power alternation between the ruling party and opposition political parties more in Nigeria relative to Ghana. It, therefore, argues that the Nigerian state more than the Ghanaian state is characterized by limited institutional autonomy which undermined orderly transfer of political power by the ruling political party to the opposition political party with implications for democratic stability. Among others, the study is of the view that the Independent National Electoral Commission be structurally and institutionally repositioned to strengthen party politics in Nigeria by regulating the activities of political parties and other important stakeholders involved in electoral process as like in Ghana.